Como fomentar los principios de actividad y creatividad al aplicar el método científico en la Escuela. Un ejemplo para la formación de maestros - Lillo Beviá, José (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The results of an experiment about the permeability of soils is commented and proposed to three groups of students of the Teacher Training School in Pontevedra. A guide for the activity is not given, but with some indications. The students design the experiment and its parts, criticize their own activity and correct their mistakes. It is verified that the richess of ideas given by the students exceeds the previsions which an ordinary teacher would do in designing the guide of a given experiment. The student does not only verify the experiment guide, but he is the designer and the critic of the investigating process. The results obtained encourage us to practise an active, creative and inexpensive methodology in the training of future teachers.